Professor Chamberlin's Theory of Limited Competition - Nichol, A. J. (Quarterly Journal of Economics, 1934)
His review of Cournot and Edgeworth does not get down to bedrock, 318.— Difficulties in his treatment of foresight (1) under conditions of decreasing variable costs, 319; the argument expressed in terms of the symbols of Cournot, 323; (2) under unequal conditions of increasing cost, 325; diagrammatic presentation, 333; nine points of conflict with his conclusions, 335.